1990
DOI: 10.1007/bf01321316
|View full text |Cite
|
Sign up to set email alerts
|

Sleep problems in the community elderly as predictors of death and nursing home placement

Abstract: In 1984-85, 1855 elderly residents of an urban community responded to a comprehensive baseline interview that included questions regarding an extensive set of sleep characteristics and problems. During the subsequent 3 1/2 years of follow-up, 16.7% of the respondents died and 3.5% were placed in nursing homes. The predictive significance of each sleep characteristic for mortality and for nursing home placement was determined separately for males and females, using Cox proportional hazards models. Selected demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
159
1
4

Year Published

1999
1999
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 274 publications
(168 citation statements)
references
References 13 publications
4
159
1
4
Order By: Relevance
“…Epidemiological studies show strong linkages between sleep loss and comorbid conditions and mortality (56,73,80; reviewed in Refs. 1 and 44) but do not establish causal relationships between regulatory processes and outcomes.…”
mentioning
confidence: 99%
“…Epidemiological studies show strong linkages between sleep loss and comorbid conditions and mortality (56,73,80; reviewed in Refs. 1 and 44) but do not establish causal relationships between regulatory processes and outcomes.…”
mentioning
confidence: 99%
“…Although there were some studies examining the relationship between sleep duration and mortality, [1][2][3][4][5][6][7][8][9][10] it has not been fully discussed. Most previous reports have found that there was a Ushaped relationship between sleep duration and all-cause mortality in both males and females.…”
mentioning
confidence: 99%
“…Many previous studies, [1][2][3][4][5][6] though not all, [7][8][9][10] reported that both long and short sleep duration increased risk of death. However, there have been only a few studies controlling for various relevant confounding factors.…”
mentioning
confidence: 99%
“…Sleep provides neurological and physiological benefits that are crucial to promoting health and bodily function [9]. No other timed activity synchrony is more important to brain plasticity and resilience than the one between sleep and the sleep/wake cycle [10].…”
Section: Introductionmentioning
confidence: 99%
“…Circadian rhythm disorders (CRDs) occur in over 60 percent of patients with Alzheimer's disease and related dementias and are associated with increased morbidity and mortality and poor quality of life [10,11]. CRD symptoms include late afternoon/evening agitation (e.g., "sundowning") and irregular sleep-wake rhythms such as daytime hypersomnia, frequent night wakenings, and poor sleep efficiency [12][13][14].…”
Section: Introductionmentioning
confidence: 99%